Nitrogen management in maize cover crop rotations - Rosolem, Ciro Antonio [UNESP]; Pace, L.; Crusciol, CAC (Kluwer Academic Publ, 2004)
Winter cover crops can affect N nutrition of the following maize crop. Although legumes have been recommend for maize rotations, in tropical areas grasses may be more interesting because they provide a longer protection of soil surface. Legumes can add N to the system and grasses can compete with maize for the available nutrient. An experiment was conducted in Botucatu, São Paulo State, Brazil, to study N dynamics in the soil surface straw-maize system as affected by N fertilization management and species included in the no-till rotation. Treatments were fallow, black oat (Avena strigosa), pearl millet (Pennisetum glaucum), white lupins (Lupinus albus), black oat fertilized with N. and pearl millet fertilized with N. Maize was grown afterwards in the same plots, receiving 0.0, 60.0 and 120.0 kg ha(-1) of N sidedressed 30 days after plant emergence. Soil, straw and maize samples were taken periodically. The highest corn yields were observed when it was cropped after pearl millet fertilized with N. Nitrogen side dressed application up to 120 kg ha(-1) was not able to avoid corn yield decrease caused by black oat. Grasses can be recommended in maize rotations in tropical areas, provided they receive nitrogen fertilizer and show no allelopathy. Due to its higher ON ratio and dry matter yield they are better than legumes, protecting the soil surface for a longer period. Pearl millet is particularly interesting because it enhances N use efficiency by the following maize crop. For a better N availability/demand synchronism, the cover crops should be desiccated right before maize planting.
Keywords: ammonium; black oat; lupin; nitrate; nitrogen use efficiency; pearl millet